Quality Assurance Practices in Public Technical and Vocational Education and Training Institutions in the Khartoum State-Sudan - Gasmelseed, Ahmed Mansour Mohammad (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2021)
The primary purpose of this study was to examine the quality assurance practice of public TVET institutions in Khartoum State and its challenges and prospects. To this end, the study used an explanatory sequential mixed method design. The researcher chooses 285 teachers and 491 students from 12 TVET institutions to complete the study questionnaire using stratified and simple random sampling. Descriptive (mean scores, standard deviation) and inferential statistics used to analyze quantitative data (two-sample t-test, multiple regression analysis). Also, the researcher interviewed all of the selected TVET institution managers, technical education directors, and SCVTA for qualitative data. Besides, six teachers and nine students participated in a focus group discussion, accompanied by an observational checklist for the quantity and quality of selected input resources. Documentary analyses for TVET policy documents were also used. According to the study's findings, the amount of materials and services available at Khartoum state TVET institutions is insufficient. In TVET institutions, the input quality was poor. Students had high expectations and perceptions of TVET.Â It was suggested that the authorities: formulate specific policies and plans for TVET, allocate the appropriate budget, and monitor the plan's implementation; form a collaboration between industry and TVET to help students and compensate for training deficiencies, and pay more attention to teacher training and motivation by meeting their needs.